The Triad of Influence: How Price, Payment, and Trust Shape Online Purchase Behavior - Adzirah Muzaffirah; Wahib Muhaimmin, Abdul; Hidayat, Kliwon; Elita Dewi, Heptari; Zulbetti, Rita; Daffa Dezar, Muhammad (Profit: Jurnal Adminsitrasi Bisnis, 2025)
Despite the growing popularity of online grocery shopping, consumers remain hesitant to purchase fresh produce online. All things that lead to practicality are straightforward to find in every business nowadays, even agricultural companies, as well as payment methods that have begun to switch to digital. This study investigates the factors influencing their purchasing decisions on the K platform. This research took place from January to March 2024. The respondents in this study amounted to 88 in The Greater Jakarta area. Data were obtained and analyzed using Structural Equation Models-Partial Least Square (SEM-PLS). Unlike prior research, we examine the moderating role of consumer trust on the relationship between price and purchasing decisions. Our findings reveal that price and payment methods significantly affect consumer purchasing decisions. However, consumer trust can mitigate the negative impact of price increases on sales. By understanding these dynamics, businesses can develop more effective strategies to attract and retain online customers in the competitive market for fresh produce.